2012
DOI: 10.1159/000343585
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Margins of Resection Influence Primary Gastrointestinal Stromal Tumor Survival

Abstract: Background: Primary gastrointestinal stromal tumors (GISTs) are stromal tumors that arise from the gastrointestinal tract. Both surgical resection and molecular therapy are crucial in the treatment of these tumors. This study analyzes the outcomes of 151 patients with GIST treated at 3 institutions. These institutions comprise the GISTologist Study Group and provided follow-up data. Patients and Methods: 151 patients with primary GIST were admitted and treated at the St. Orsola-Malpighi University Hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…While in one study a microscopically positive margin was not found to be a significant adverse factor 55 , another study found it an adverse factor for survival. 56 Localized intestinal GISTs are handled with segmental resections. Laparosopic surgery is increasingly used for small or medium- sized GISTs (at least up to 5 cm).…”
Section: Comments On Gist Surgerymentioning
confidence: 99%
“…While in one study a microscopically positive margin was not found to be a significant adverse factor 55 , another study found it an adverse factor for survival. 56 Localized intestinal GISTs are handled with segmental resections. Laparosopic surgery is increasingly used for small or medium- sized GISTs (at least up to 5 cm).…”
Section: Comments On Gist Surgerymentioning
confidence: 99%
“…Controversial data exist as to the issue of the prognostic relevance of surgical margins. While complete, margin-negative (R0) tumor excision remains the goal of GIST surgery and an increased recurrence rate might be expected following resection with tumor-involved margins, this was not confirmed in all studies [37,38]. Therefore, if examination of the surgical specimen reveals microscopically tumor-positive margins, reoperation should only be attempted if the original site of the involved margin can be identified and its excision does not cause major functional sequelae and is not associated with undue operative risk; however, the paucity of data regarding this issue makes this decision a highly individual one.…”
Section: Management Of Localized Gistsmentioning
confidence: 99%
“…Of the 19 articles, 2 were excluded due to the insufficient reported data for the estimation of HR, 3 were excluded because they put R1 resection and R2 resection together, and 2 were excluded due to the small sample size (there are only 2 cases with R1 margin in both studies) 17 18 . Finally, a total of 12 studies 14 15 16 19 20 21 22 23 24 25 26 27 were included in this meta-analysis. Literatures screening process was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, given that GISTs often abut some vital structures such as gastroesophageal junction, duodenal papilla as well as retroperitoneal vessels, R1 margins are acceptable especially for low-risk lesions when R0 resection might imply major functional sequelae 11 14 . However, other reports support positive microscopic margins (R1) as a main prognostic factor of tumor recurrence 15 16 .…”
mentioning
confidence: 99%